2021
DOI: 10.3389/fpubh.2020.614631
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Determinants of a Workplace Health Promotion? Application of a Social Marketing Model in Identifying Determinants of Physical Activity in the Workplace (a Qualitative Study)

Abstract: Background and objective: Physical activity is an important behavior to reduce the risk of non-communicable diseases. Providing the context for physical activity in the workplace in addition to promoting the employees' physical and mental health has significant economic benefits for organizations. We conducted the present study using a social marketing model to explain the determinants of a Workplace Health Promotion in promoting physical activity among employees of government organizations in Yasuj, Iran.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…The peer checks to achieve the confirmability, results were checked with some of the other people like teachers and students, who did not participate in the research, and they confirmed the fitness of the results as well. And in our study, expression of research limitations and comparison of findings from a participant to another during the research and paying attention to the greater diversity of participants in terms of age, marital status, educational level, and job status contributed to achieve the transferability [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peer checks to achieve the confirmability, results were checked with some of the other people like teachers and students, who did not participate in the research, and they confirmed the fitness of the results as well. And in our study, expression of research limitations and comparison of findings from a participant to another during the research and paying attention to the greater diversity of participants in terms of age, marital status, educational level, and job status contributed to achieve the transferability [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, finding reasons to focus on the issue and identifying obstacles and solutions for them are effective strategies in this respect [ 16 , 17 ]. Understanding these key factors is possible by doing qualitative research as a necessary step [ 18 ]. In general, qualitative research is used to have a deep understanding of the target population's viewpoints and opinions in the texture and environment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dicha complejidad, sumado a la cultura organizacional que demandaba una cadena de autorizaciones entre diferentes niveles jerárquicos, podía funcionar como barrera para la comunicación y la participación de los trabajadores. La falta de apoyo desde el nivel gerencial es un factor que incide en el impacto y la adecuada implementación de intervenciones en ámbitos laborales 15,27,29,30 . La inclusión de un componente complementario, consistente en la comunicación dirigida a estos niveles gerenciales intermedios, apuntó a conseguir un mayor involucramiento y apoyo de estos actores clave.…”
Section: Estrategiasunclassified
“…La implementación de intervenciones de prevención y promoción de la salud en ámbitos laborales tienen un enorme potencial, y a su vez presentan desafíos particulares, debido a la necesidad de adaptar y compatibilizar los programas preventivos a la cultura de las organizaciones y a la necesidad de lograr la aceptación y compromiso, tanto de los trabajadores que serán población objetivo, como de quienes dentro de las instituciones apoyarán o facilitarán el funcionamiento de estos programas 14,15 . En estos ámbitos, las evaluaciones formativas tienen una gran importancia para mejorar las oportunidades de éxito de las intervenciones y para adaptarlas a los recursos y necesidades de las instituciones y sus trabajadores 29,30 .…”
Section: Estrategiasunclassified
“…The workplace is complex, with multiple factors and determinants that influence physical activity [ 18 , 19 ]. For shift workers, lack of time and work-related fatigue may explain workers’ low levels of physical activity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%